Aquatic insects (Ephemeroptera, Plecoptera, Trichoptera and Diptera: Tipuloidea) from the upper Neretva in Bosnia-Herzegovina - Wolfram Graf; Ernst Bauernfeind; Marija Ivković; Levente-Péter Kolcsár (Natura Sloveniae)
Within the upper Neretva catchment in Bosnia several hydropower plants are projected. Between 28.6. and 1.7.2022 a baseline survey was initiated to screen the area regarding the diversity of aquatic insects and its linked conservation value. In total, 59 Trichoptera species, ten Plecoptera species, 19 Ephemeroptera and 16 Diptera (Tipuloidea) species were collected, of which Baeoura sp. is new to science. 35 species are endemics of the Balkans, most species are rheobiontic and need high water current. The most abundant taxa are species of the trichopteran genus Agapetus (A. slavorum and A. ochripes) – surface grazers sensitive to water fluctuations and therefore vulnerable to hydropower-induced water level changes. With estimated 40,000 attracted specimens per night, light traps were extraordinarily successful. The extremely high diversity, as well as the enormous abundance of aquatic insects, underline the importance of the upper Neretva as an unimpacted riverine system embedded in dense natural and near-natural forest.